The Influence of the Level of Education and Training on the Performance of Village Officials in Tebing Syahbandar District : (Case Study of Village Secretaries, Heads of Affairs and Heads of Sections) - Jopinus Saragih (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
This research aims to determine and analyze the influence of education and training levels on the performance of village officials in Tebing Syahbandar District. The data used is primary data. The sample studied was 50 respondents. Data obtained from respondents usingSPSS version 17.00. The research results show thatMultiple linear regression equation Y = 10.984 + 0.56X1 +0.575X2. Meanwhile, based on the coefficient of determination, the variable level of education and training influences the performance of village officials by 0.297 or 29.7%. and the remaining 0.703 or 70.3% is explained by other variables outside this research model. The hypothesis results show that the level of education has no partial effect on the performance of village officials. This can be seen from table 4.13, where the tcount value is tcount (0.634) < ttable (2.010), likewise with the significance value of 0.529 > 0.05, it can be concluded that the first hypothesis is rejected. The training variable partially influences the performance of village officials. This can be seen from table 4.13, the tcount value (3,881) > ttable (2.010), and the significance value is 0.000< 0.05 then it can be concluded that the second hypothesis is accepted. The Fcount value (11.339) > Ftable (3.20), and the significance value is 0.000 < 0.05, it can be concluded that the third hypothesis is accepted, meaningThe Education Level Variable (X1) and the Training Variable (X2) have a joint (simultaneous) effect on the Performance Variable (Y).